Iterative Method for Railway Wheel Profile Design - Juraj Gerlici; Tomas Lack (Communications - Scientific letters of the University of Zilina, 2009)
The presented article deals with the methods for the railway wheel profile development on the base of the intended shape of wheelset/track contact geometric characteristics. The article deals with two methods. In short the profiles creation method through arcs radii profile variation is mentioned. The main emphasis is directed to the “Iterative method for a railway wheel profile design”. This method is explained in a more detailed way in the article. The base for the creation of new profiles with the help of the first method is an interactive attitude based on the modification of the original shape which is defined by section of a railway wheel profile, with interconnected and exactly defined arcs radii. It is possible to change them according to shape needs of the final geometrical characteristics. The base of the iterative method, which is of the highest importance in this article, is to develop a new profile under given conditions – a prescribed shape of the contact points distribution and the shape of delta-r function. The newly developed wheel profile in the couple with given rail profile will have requested chosen characteristic shapes.